Benthic sediment nitrogen transformation processes in Arctic Kongsfjorden subject to glacier discharge - Guo, Mengjie; Wang, Qing; Zhang, Wanying; Jiao, Yi; Zhou, Zeming; Hou, Lijun; Zhu, Renbin (Polar biology, 2024)
The Arctic fjords are currently experiencing the effects of glacier discharge, which may affect the nitrogen cycle and associated microbial communities in the benthic sediments. However, there remain a lack of understanding regarding nitrogen transformation processes in Arctic fjords. Here, we collected benthic sediment samples from Arctic Kongsfjorden subject to glacier discharge and then examined the spatial variability in the biogeochemical properties, nitrogen transformation processes and associated microbial community structures. Results showed that potential nitrogen transformation rates showed significant spatial differences ( P < 0.05), and no significant correlation ( P > 0.05) with TOC, TN, NH 4 + -N, NO 3 −-N, and NO 2 − -N in benthic sediments. Relatively higher contributions of anammox to nitrogen removal (48.5–62.7%) and DNRA to nitrate reduction (27.3–67.3%) occurred in Kongsfjorden sediments, compared with most of marine sediments. The gene abundances of AOB amo A, anammox 16S rRNA, and nir S showed significant positive correlations ( P < 0.05) with TOC:N, TOC, TN, and TP in the sediments. All detected ammonia-oxidizing archaea (AOA) belonged to the group 1.1a Nitrosopumilus cluster with the group 1.1b Nitrososphaera cluster at the site closest to the glacier. The detected ammonia-oxidizing bacteria (AOB) and anammox bacteria belongs to β -Proteobacteria Nitrosospira and Planctomycetes Candidatus Scalindua , respectively. AOB has a comparative advantage over AOA in the Kongsfjorden sediments. Overall, our results indicated that the glacier discharge had an important effect on the biogeochemical properties of the Kongsfjorden sediments, which further influenced benthic potential nitrogen transformation rates and associated microbial communities.